Pemetaan Pola Persaingan dan Konsentrasi Industri - Manzilati, Asfi; Wildana, Muhammad Dandy Alif; Syamsuri, Asyila Muthi'ah; Nabila, Ulfa (Jurnal Pendidikan Ekonomi Undiksha, 2024)
The Indonesian government, in its capacity as a regulator, has established a Business Competition Supervisory Commission, which has the task of ensuring that competition between industrial players in Indonesia runs healthily. The results of this research are that, first, digitalization is able to influence people's trust in storing their assets in a financial institution. Second, the mapping of the market leader in the mining industry is controlled by companies operating in the bauxite and mineral sectors based on the number of assets and profit and loss owned by the company as well as the company's low expenses so that it can expand market share. Third, mapping the manufacturing industry, which experienced a significant decline in profits during the pandemic, one of which was the Garuda Indonesia Company, but in 2021 it began to experience an increase, but this is different with Telkom Indonesia, which experienced an increase in profits during the pandemic due to changes in lifestyle. online to offline.